2009
DOI: 10.1051/agro:2008051
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of genetically modified (GM) and non-GM crops in the European Union. A review

Abstract: -The adoption of genetically modified (GM) crops in the European Union (EU) raises questions on the feasibility of coexistence between GM and non-GM crops. Regulations to ensure that different cropping systems can develop side-by-side without excluding any agricultural option are currently implemented or developed by member states. The aim of this review is to explore whether nationally or regionally proposed coexistence strategies comply with the general principles established by the European Commission that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
0
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 123 publications
6
134
0
4
Order By: Relevance
“…However, studies comparing results of these experiments found that cross-fertilization patterns are similar, notwithstanding differences in experimental approaches (Riesgo et al, 2010;Sanvido et al, 2008). In spite of similar patterns for cross-fertilization events, isolation distance between GM and non-GM maize mandated by different EU countries differ greatly, ranging from 25 to 600 m (Riesgo et al, 2010), even though they share the guidelines on GM foods labeling (EC N • 1829/2003) (Devos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies comparing results of these experiments found that cross-fertilization patterns are similar, notwithstanding differences in experimental approaches (Riesgo et al, 2010;Sanvido et al, 2008). In spite of similar patterns for cross-fertilization events, isolation distance between GM and non-GM maize mandated by different EU countries differ greatly, ranging from 25 to 600 m (Riesgo et al, 2010), even though they share the guidelines on GM foods labeling (EC N • 1829/2003) (Devos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless pollen grains of maize are large and heavy in comparison with those of other wind-pollinated species and its flight distance is limited to a short range. Taking into account also this characteristic, different isolation distances between the conventional and GM maize and organic and GM maize, respectively, have been adapted in the EU member states (Devos et al 2009). The isolation distances 200 m between the conventional and GM maize and 300 m between the organic and GM maize were adopted in Slovakia and farmers are allowed to replace the mandatory isolation distance by border rows of conventional maize according to the principle: 1 border row can replace 2 m of the isolation distance.…”
mentioning
confidence: 99%
“…These safety margins differ considerably across EU member states. GM maize, for instance, has a minimum distance requirement ranging from 25 m in Sweden to 800 m in Luxembourg, although scientific evidence does not call for such distances larger than 15-50 m [14].…”
Section: Foregone Costs Of Coexistence Measuresmentioning
confidence: 99%
“…One may even question the necessity for coexistence regulations from an economic point of view [12]. The pros and cons have been addressed by a number of authors [1,8,10,11,[13][14][15]. As coexistence requirements are politically motivated, we hardly can expect cultivation of GM tomato and GM eggplants to be possible without coexistence regulations.…”
Section: Introductionmentioning
confidence: 99%